OS SABERES MATEIROS DAS COMUNIDADES TRADICIONAIS DA REGIÃO SERRA DAS ALMAS, PARANÁ: HISTÓRIAS DE VIDA E PAISAGENS - Staniski, Adelita (2016)
This work has the objective to understand the woodsmen knowledge in socio-ecological transformation process of rural communities in the region Serra das Almas, Paraná. Considering the experience and perception of the forest on the local socio-spatial context, the present study is divided into seven chapters. In theoretical reflection we approached the forms of knowledge and know-how and woodsman as studies ethnobotanical can assist the dialogue of knowledge. To investigate the literature raises the question of intellectual cultural heritage which often ends up being incorporated into databases without due recognition and regulation of this access information. If part then to an analysis of the relationship of communities with the Araucaria forest and how the law regulates and influences the configuration of landscapes. As regards the method began with an exploratory survey seeking an approximation to reality studied, then interviews were conducted using the technique of oral history of life, paths through the forest, collecting botanical material and observation. It is concluded that the three communities use tree species in their day-to - day and have in common strong religiosity. Regarding the process of transforming the region of Serra das Almas appeared as a rural dynamic where some practices and knowledge remain, others turn and some live only in the memory of former residents of the locality.